The Design and Simulation of Fuzzy PID Parameter Self-tuning Controller - Wei Xie; Jianmin Duan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Based on parameter self-tuning fuzzy PID controller, a fuzzy inference method is utilized to realize automatic regulating PID parameter, and the application of the controller in a system is studied with MATLAB in this paper. The combination of PID controller system and fuzzy controller system combines the convenience of PID control together with the flexibility of fuzzy control, and takes advantage of the traditional control, which has a great practical significance. The results of simulation show that fuzzy PID parameter self-tuning controller has a better control effect than the traditional one, and can improve the static and dynamic properties of the system well. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7674